Assessing a Common Currency in Africa (The Thinker)
A common currency is a necessary condition for the realisation of the benefits of integration. The adoption of a single currency exposes domestic markets to foreign markets, thereby increasing competition between member countries and enhancing the competitiveness of national industries (Saka, Onafowokan and Adebayo, 2015). A common currency is the signification of an economic community and a united and developed people. The importance of African economies in global trade is not going to be judged by the power of each country’s individual economy, for there is none, so far, or by the stability provided by the benevolent hegemony of a colonial master. Rather, the power of African economies lies in the actual share of the proposed currency in world official foreign reserves, its liquidity in international trade, and its role as a competitor against the exorbitant U.S. dollar.